The problem of forensic veterinary examination of small animal corpses in cases of mechanical asphyxia - Borysevich, B.; Kruchynenko, O.; Peredera, О. (Scientific Progress & Innovations, 2024)
The article provides an overview of theoretical information and methodological approaches to the problem of forensic veterinary examination of animal corpses that died as a result of mechanical asphyxiation. In veterinary practice, there are cases of death of animals due to ingestion of various media, objects, and neck compression from the outside. This phenomenon is called mechanical asphyxia. Most often, such cases occur in dogs and cats and are associated with animal cruelty, including cases of domestic violence, when the aggression of a person with inappropriate behavior extends to animals kept in human homes. Such actions fall under an offense for which the perpetrators of such a crime are criminally liable under Ukrainian law. This article provides a list of known types of mechanical asphyxia and situations that lead to this condition in animals. An overview of the etiologic factors and pathogenic mechanisms characteristic of mechanical asphyxia is given. The pathological, anatomical and histological changes in mechanical asphyxia are shown, and the range of questions that law enforcement officials ask a specialist who conducts forensic veterinary examination in such cases is presented. The general signs characteristic of mechanical asphyxia are shown, including a special appearance of cadaveric spots, cyanosis, pinpoint hemorrhages on certain serous and mucous membranes, asphyxiated blood, and some others. The article describes changes in strangulation asphyxia, situations in which it can occur, and its characteristic morphological features, with cases from the practice of the institutions where the authors of the study work. The features of the strangulation furrow found in animal cadavers are presented. The circumstances under which compression asphyxia occurs in animals, the mechanisms of its development and the characteristic pathological and anatomical changes in animals that died from it are shown. The features of asphyxia in a limited confined space and situations in which this phenomenon occurs are characterized. The features of the strangulation furrow found in animal cadavers are presented. The circumstances under which compression asphyxia occurs in animals, the mechanisms of its development and the characteristic pathological and anatomical changes in animals that died from it are shown. The features of asphyxia in a limited confined space and situations in which this phenomenon occurs are characterized.